Bygone badass broads : 52 forgotten women who changed the world - Lee, Mackenzi (Abrams Image, 2018)
Based on Mackenzi Lee<U+2019>s popular weekly Twitter series of the same name, Bygone Badass Broads features 52 remarkable and forgotten trailblazing women from all over the world. With tales of heroism and cunning, in-depth bios and witty storytelling, Bygone Badass Broads gives new life to these historic female pioneers. Starting in the fifth century BC and continuing to the present, the book takes a closer look at bold and inspiring women who dared to step outside the traditional gender roles of their time. Coupled with riveting illustrations and Lee<U+2019>s humorous and conversational storytelling style, this book is an outright celebration of the badass women who paved the way for the rest of us.